1989
DOI: 10.1056/nejm198910053211406
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Transfusion-Associated Infection with Human Immunodeficiency Virus

Abstract: Patients infected by the human immunodeficiency virus (HIV) as a result of blood transfusions are unique in that their dates of infection are well defined and their medical conditions before infection are known. To characterize the natural history of transfusion-associated HIV infection, we studied 694 recipients of blood from 112 donors in whom AIDS later developed and from 31 donors later found to be positive for HIV antibody. Of the recipients tested, 85 were seronegative, 116 were seropositive, and 19 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
1
2

Year Published

1989
1989
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(61 citation statements)
references
References 20 publications
0
58
1
2
Order By: Relevance
“…In one study, the chance of infection was reported to rise substantially if the donor developed AIDS in 2 to 3 years after donation (913). Other studies have shown that individuals receiving blood from donors who subsequently develop AIDS within 29 months have a greater chance of progressing to disease than those recipients of infected blood from donors who become symptomatic after this period (1249). This latter finding could reflect the amount of virus present and/or the biologic properties of the virus in the donated blood (e.g., more virulent) (see Sections IV A and XVI D).…”
Section: Transmission By Blood and Blood Productsmentioning
confidence: 95%
“…In one study, the chance of infection was reported to rise substantially if the donor developed AIDS in 2 to 3 years after donation (913). Other studies have shown that individuals receiving blood from donors who subsequently develop AIDS within 29 months have a greater chance of progressing to disease than those recipients of infected blood from donors who become symptomatic after this period (1249). This latter finding could reflect the amount of virus present and/or the biologic properties of the virus in the donated blood (e.g., more virulent) (see Sections IV A and XVI D).…”
Section: Transmission By Blood and Blood Productsmentioning
confidence: 95%
“…The relative risk of infection by HIV correlates directly with the number of exposures to the virus (1,2). However, within any exposed uninfected (EU) population, some individuals remain uninfected despite multiple unprotected encounters with HIV-infected partners.…”
mentioning
confidence: 99%
“…It is likely that new advances in the management of individuals with HIV infection will influence these distributions. Further, changes in the incubation period distribution could occur even in the absence of changes in available treatments and treatment uptake, due to the evolving distributions of new viral strains in HIV-infected persons [3,4]. It is therefore important to monitor whether there are changes in the incubation period distribution and, if so, the extent of those changes and factors associated with them.…”
Section: Background and Objectivesmentioning
confidence: 99%